Problematics of Determining Interest in Peer-to-peer Lending in Indonesia - Annas, Muhammad; Anshori, Muhammad Anwar (Jurnal Media Hukum, 2021)
Peer-to-peer lending is considered as the solution for people who require loans with easy terms. However, peer-to-peer lending in Indonesia causes some new problem related to the essential nature of it. Authorization of Indonesian Joint Funding Fintech (AFPI) determines peer-to-peer lending interest-debt possible to violate competition law in Indonesia. The paper aims to describe and analyze the authorization of Indonesian Joint Funding Fintech, which has a big chance to harm competition law in Indonesia. The author uses normative legal research methods and secondary data sources to examine the topic in this study. The result shows that the arrangement of interest-debt in peer-to-peer lending potentially creates a cartel and violates the basic principles of competition law in Indonesia.